Integrasi Nilai Tarbawi dalam Kurikulum Islam Berbasis Emosional 4.0 - Nisa, Ainun; Wahyuni, Desta Tri; Ghani, A.; Akmansyah, Muhammad; Amirudin, Amirudin (Universitas Muhammadiyah Magelang, 2025)
The current phenomenon in Islamic education shows a shift in learning orientation that tends to emphasize cognitive and academic aspects, while spiritual and emotional dimensions are often neglected. Many students experience a void in the meaning of learning, weak social empathy, and low moral awareness amid the rapid flow of digitalization and global competition. This condition indicates the need for a curriculum reconstruction that not only transfers knowledge but also fosters emotional and spiritual intelligence based on tarbawi values. This study aims to analyze the concept of integrating tarbawi values into an emotional 4.0-based Islamic curriculum as a strategy for character building and spiritual balance for students in the digital age. The research method used is descriptive qualitative through a library research approach, with analysis of classical and contemporary literature related to Islamic education, tarbawi values, and emotional intelligence theory. The results of the study show that the integration of tarbawi values such as sincerity, patience, trustworthiness, and empathy in the Islamic curriculum can optimize the affective aspects of students and strengthen the dimension of spirituality in line with the needs of the 21st century. The Emotional 4.0-based Islamic curriculum requires educators to be uswah hasanah and able to manage value-based, technology-based, and empathy-based learning. Thus, integrative and emotional Islamic education can produce a generation that is faithful, knowledgeable, and has noble character that is adaptive to the developments of the times.